Seed dormancy and persistent sediment seed banks of ephemeral freshwater rock pools in the Australian monsoon tropics - Cross, A.; Turner, S.; Renton, M.; Baskin, J.; Dixon, Kingsley; Merritt, D. (Oxford University Press, 2015)
Background and Aims: Rock pools are small, geologically stable freshwater ecosystems that are both hydrologically and biologically isolated. They harbour high levels of plant endemism and experience environmental unpredictability driven by the presence of water over variable temporal scales. This study examined the hypothesis that the sediment seed bank in monsoon tropical freshwater rock pools would persist through one or more periods of desiccation, with seed dormancy regulating germination timing in response to rock pool inundation and drying events. Methods: Seeds were collected from seven dominant rock pool species, and germination biology and seed dormancy were assessed under laboratory conditions in response to light, temperature and germination stimulators (gibberellic acid, karrikinolide and ethylene). Field surveys of seedling emergence from freshwater rock pools in the Kimberley region of Western Australia were undertaken, and sediment samples were collected from 41 vegetated rock pools. Seedling emergence and seed bank persistence in response to multiple wetting and drying cycles were determined.Key Results: The sediment seed bank of individual rock pools was large (13 824 ± 307 to 218 320 ± 42 412 seeds m−2 for the five species investigated) and spatially variable. Seedling density for these same species in the field ranged from 13 696 to 87 232 seedlings m−2. Seeds of rock pool taxa were physiologically dormant, with germination promoted by after-ripening and exposure to ethylene or karrikinolide. Patterns of seedling emergence varied between species and were finely tuned to seasonal temperature and moisture conditions, with the proportions of emergent seedlings differing between species through multiple inundation events. A viable seed bank persisted after ten consecutive laboratory inundation events, and seeds retained viability in dry sediments for at least 3 years